Controle coerente da dinâmica de excitons qubit em cavidades ressonantes - Freitas Neto, Antonio de (2017)
In this work, we demonstrate theoretically how to use a Gaussian-shaped pulse to control the population inversion in a system composed of a quantum dot treated as a two-level system inserted in resonant nanocavity. For this, we use the Jaynes-Cummings model to describe the system, however, dissipative processes should not be neglected, which were included through the operators of Lindbla. In this sense, we demonstrate how to prepare the system to control population inversion, considering as initial state the superposition of the exciton in the ground state with the cavity in the coherent state. So, we analyze the effects of the dephasing between the cavity and the exciton frequency, as well as, the action of a continuous laser acting exclusively in the cavity generating a protection to the dissipative processes related to the imperfect surface of the cavity. We analyzed the process of exchanging information between two quantum dots coupled through Foster using coherent pulse exclusively at one of the dot and verified the information exchange by means of the inversion of population in the quantum dot unpumped.